EXPLORING THE ROLE OF REBRANDING, SERVICE QUALITY, AND BRAND IMAGE IN HOTEL CUSTOMER SATISFACTION AT HARRIS HOTEL PONTIANAK - Florentina, Ika; Patiro , Shine Pintor Siolemba; Mubarok, Faizul (Management Department, Faculty of Economics and Business, Universitas Jambi, 2025)
This study aims to analyze the influence of rebranding, service quality, and brand image on customer satisfaction at Harris Hotel Pontianak. The research background arises from the increasingly intense competition in the hospitality industry, where marketing strategies based on rebranding and service quality play a crucial role in maintaining customer loyalty. This study employed a quantitative approach using a survey method. Data were collected through questionnaires distributed to 130 respondents, consisting of guests of Harris Hotel Pontianak. The analytical technique applied was multiple linear regression to examine the effect of independent variables on the dependent variable. The results reveal that rebranding, service quality, and brand image simultaneously have a significant effect on customer satisfaction. Partially, service quality exerts the most dominant influence, followed by brand image, while rebranding shows a weaker effect compared to the other two variables. These findings indicate that although rebranding is important in shaping new consumer perceptions, customer satisfaction is more strongly determined by the quality of services provided and the strength of the established brand image. The study concludes that hotel management should prioritize consistent improvements in service quality, strengthen brand image through effective marketing communication, and carry out continuous rebranding efforts to remain relevant to market needs. This research is expected to serve as a reference for hospitality practitioners in formulating customer satisfaction-oriented marketing strategies. Keywords: rebranding, service quality, brand image